Bilateral atypical ovarian masses: don’t overlook a functional gonadotropic pituitary adenoma - Hagege, Estelle; Vitellius, Geraldine; Fevre, Anne; Mostaert, Malorie; Litre, Fabien; Graesslin, Olivier; Pirtea, Paul; Delemer, Brigitte (Frontiers in Endocrinology, 2025)
Functional gonadotroph adenoma (FGA) is a rare condition associated with secretion of biologically active gonadotropins which affect reproductive organs. In women of reproductive age, it has been reported as a cause of spontaneous ovarian hyperstimulation syndrome (OHSS) occurring outside the context of assisted reproductive technology (ART). In rare instances, FGA may present as suspicious ovarian masses, leading to an overlooked pituitary disorder. We report the case of a 34-year-old woman initially suspected of having a bilateral ovarian tumor with a borderline component due to thick-walled cystic masses. She underwent pelvic surgery, resulting in an oophorectomy. However, a few weeks postoperatively, the sudden onset of galactorrhea prompted further investigation, revealing hyperprolactinemia, FSH hypersecretion, and low LH levels. Ultimately, the diagnosis of FGA was established. A literature review was conducted to analyze similar cases where patients underwent ovarian surgery without prior hormonal assessment or suspicion of pituitary pathology, only to be diagnosed with FGA later. Thirteen additional cases were identified, including ovarian cysts and two cases of suspicious ovarian masses, with diagnostic delays ranging from 1.5 to 10 years. This case highlights the importance of considering FGA in the differential diagnosis of bilateral ovarian masses to avoid unnecessary surgical procedures.